Lavender Aromatherapy on Post-Partum Anxiety - Dewi Sulastri, Siti; Shinta, Novelia; J Wowor, Tommy (Rajaki of Tulip Medika Publisher, 2023)
Background: Anxiety that is not immediately treated will result in port partum depression, postpartum blues or baby blues. The safest treatment of anxiety is to use non-pharmacological methods; one of which is lavender aromatherapy. Objective: The research aims to determine the effect of lavender aromatherapy on the anxiety of post-partum women at BPM Elis Nurhayati (Independent Midwife Clinic) Depok in 2018. Methods: The study used Quasy-Experiment with nonequivalent control group and pre-post test design. The research involved two groups, the experimental group and the control group. Data were collected using Hamilton Rating Scale for Anxiety questionnaire (HRS-A). Data analysis was carried out using independent and paired simple t-test. Results: Statistical result shows that P value was 0.000, it means that there was an influence of lavender aromatherapy in decreasing anxiety among post-partum women. Conclusions and Suggestions: Medical officers need to optimize treatment to reduce the level of post-partum anxiety by giving lavender aromatherapy for 15-30 minutes. Lavender aromatherapy is suggested to use to reduce postpartum anxiety.